Islamic Bank Performance (Maqasid Sharia Approach) - Inten Meutia; Shelly Febriana; Eka Meirawati (Integrated Journal of Business and Economics (IJBE), 2020)
This study aims to analyze the performance of Islamic banks in Indonesia from the perspective of Maqasid Sharia. For this reason, this study uses two approaches, namely Maqasid Based Performance Evaluation Model (MPEM) and Performance Measurement based on Islamic Maqasid (PMMS). The use of these two approaches is to determine which approach is more appropriate for measuring the performance of Islamic banks. This research is a comparative study that will use a content analysis approach in exploring and analyzing Islamic bank performance data derived from annual reports. To identify bank performance, this study uses data sourced from the annual reports of 9 Islamic Commercial Banks in Indonesia for the period 2016 to 2019. A total of 36 annual reports analyzed in this study. The comparative analysis shows that performance measurement using the MPEM method resulted in higher performance outcomes than the PMMS method. This result proved significant at the five percent  level.